Managing Global Innovation Uncovering the Secrets of Future Competitiveness - Boutellier, Roman; Gassmann, Oliver; von Zedtwitz, Maximilian (Springer Berlin Heidelberg : Imprint: Springer, 2008)
What are the secrets of competitive R&D on a global scale? Based on empirical research with hundreds of R&D executives from more than 80 companies and 1000 R&D laboratories, the authors present new concepts and trends in global R&D management. Case studies from 22 best-practice companies illustrate how to put these concepts into practice. Adding new examples and management models, this third edition has been completely revised and updated incorporating emerging themes in R&D such as intellectual property management, innovation in China and India, technology listening posts, and leading R&D centers. "A wealth of data followed by thorough analysis. A must read for R&D managers and business leaders." Frans J.A.M. Greidanus, Senior Vice President, Philips Research "... a book whose rich trove of examples will inform the thinking of any manager who must think strategically about how to get the most out of R&D resources that are scattered globally. With the rise of knowledge hubs throughout the world, this third edition is especially timely." Philip Anderson, Professor, INSEAD "An insightful and thorough work on the development of global innovation that identifies key strategies and perspectives with relevant and important lessons for those venturing into the global R&D arena .... and hit the mark for those of us who have been in the middle of building this architecture." Dr. Richard Carpenter, Global R&D Director, Procter and Gamble.